The Implementation of Classroom Management Strategies by Teachers and Students to Enhance Effective Learning - Nurfaizah, Siti; U, Usman; Qaddafi, Muhammad (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Classroom management is a critical factor in ensuring that the learning process is effective, orderly, and engaging. Teachers face various challenges, including the diversity of student characteristics and the dynamic nature of the classroom, which demand the use of adaptive, creative, and responsive management strategies. This study is motivated by the need for a thorough understanding of the components, strategies, effectiveness, and challenges of classroom management. Using a qualitative approach through a literature review, the research examines academic sources addressing both the theoretical foundations and practical applications of classroom management. The findings reveal that effective classroom management requires the integration of time management, classroom organization, and student behavior regulation, combined with the implementation of proactive, responsive, and innovative strategies suited to the classroom context. These results suggest that systematic and adaptive classroom management strategies are essential for creating a conducive learning environment, enhancing student motivation, and achieving optimal learning outcomes.